Positioning of young Brazilian radios in social networks: interactivity strategies and actions - Prata, Nair; Lopez, Débora Cristina; Freire, Marcelo; Avelar, Kamilla; Diehl, Danielle (Media & Jornalismo, 2019)
Brazilian radio, inserted in the new media ecology, faces diverse challenges, assuming different configurations in front of the scenario of constant technological development. Given the context, this article turns its attention to the positioning on Facebook of three Brazilian radio stations, namely Radio Mix, Rádio Jovem Pan and Radio Transamérica. Using the methodology of content analysis in social networks and the comparative case study (Yin, 2001), the objective is to understand the main strategies of posting and engagement used by the broadcasters to capture the attention of the audience in social networks. The results point to the lack of strategy and low engagement in fanpages. None of the analyzed stations builds an effective process of interaction in their social networks, predominating the participation, characteristic of the young radio of the years 1990.